Paciente masculino de 60 años de edad con diagnóstico de cáncer pulmonar. - Paredes Gavilánez, Zully Juleidy (2021)
Lung cancer is the leading cause of death compared to other types of cancer. Symptoms range from cough, general malaise, weight loss, and lesser onset hemoptysis. Its diagnosis is given by chest x-rays or CT, and its confirmation is through a biopsy. Although surgery can also be performed, but that depending on the state of the disease. Treatment is based on surgery, chemotherapy, radiation therapy, or a combination of all of them. Its survival is approximately 5 years depending on the patient. The risk of lung cancer increases due to exposure to toxins and smoking. Other possible or confirmed risk factors include air pollution, smoking marijuana, constant and temporary exposure to cigarette smoke and the relationship to carcinogens such as asbestos, radiation, radon, arsenic, chromates, nickel , chloromethyl ethers, polycyclic aromatic hydrocarbons, also mustard gas, coke oven emissions, old stoves, and heating in huts or cabins, among many others.